Giant Appendicular Mucinous Cystoadenoma: Case Report and Review of the Literature - Oscar Josue Montes Aguilar; Angel Medina Andrade; Gerardo Perez; Stephanie Serrano Collazos; Brenda Ruiz; Maria Fernanda Chein Vazquez; Karina Yolanda Vite Pineda; Eduardo Vidrio Duarte; Carlos Eduardo Rodriguez Rodriguez; Lizette Blanco Aguilar (Archives of Clinical Gastroenterology - Peertechz Publications, 2016)
Background: Appendix tumours present an incidence of 0.2 to 0.3% among all appendectomies. It is a rare condition, commonly found as an incidental diagnosis by imaging studies due to his lack of symptoms; nevertheless it is associated with many complications when undiagnosed like pseudomixoma peritonei a condition with high morbidity and mortality. This is the importance of recognize it to establish an opportune diagnose and treatment. Case: A 49-year old man with abdominal pain of 6 days of evolution. He has medical history of diabetes mellitus 2 and hypertension. He presents to the emergency department complaining of pain in right lower quadrant and reports radiation to the ipsilateral renal fossa. Ultrasonography demonstrated an oblique cystic fusiform lesion suspicious of abscess. Simple computed tomography concluded probable mesenteric cyst. An exploratory laparotomy was performed finding a 12 X 8cm tumour lesion that protruded from the appendix. Tumour was dissected and a right hemicolectomy with side-end ileocolic anastomosis was performed. The histopathology study reveals an appendiceal mucinous neoplasm of low grade. After 5 days the patient was discharged without complications.After 8 months follow up the patients is asymptomatic and without evidence of tumour activity. Conclusion: Appendix tumours are a rare pathology with an insidious presentation representing a difficult diagnosis; requiring high index of suspect and knowledge about the correct surgical management to obtain better outcomes.